Recovery of Drug Delivery Nanoparticles from Human Plasma Using an Electrokinetic Platform Technology. Issue 38 (14th August 2015) - Ibsen, Stuart; Sonnenberg, Avery; Schutt, Carolyn; Mukthavaram, Rajesh; Yeh, Yasan; Ortac, Inanc; Manouchehri, Sareh; Kesari, Santosh; Esener, Sadik; Heller, Michael J.
<x xml:space="preserve">Abstract</x> The effect of complex biological fluids on the surface and structure of nanoparticles is a rapidly expanding field of study. One of the challenges holding back this research is the difficulty of recovering therapeutic nanoparticles from biological samples due to their small size, low density, and stealth surface coatings. Here, the first demonstration of the recovery and analysis of drug delivery nanoparticles from undiluted human plasma samples through the use of a new electrokinetic platform technology is presented. The particles are recovered from plasma through a dielectrophoresis separation force that is created by innate differences in the dielectric properties between the unaltered nanoparticles and the surrounding plasma. It is shown that this can be applied to a wide range of drug delivery nanoparticles of different morphologies and materials, including low‐density nanoliposomes. These recovered particles can then be analyzed using different methods including scanning electron microscopy to monitor surface and structural changes that result from plasma exposure. This new recovery technique can be broadly applied to the recovery of nanoparticles from high conductance fluids in a wide range of applications.